Analisis Faktor-Faktor yang Mempengaruhi Surflus Underwriting Dana Tabarru' Studi Kasus AJB BumiPutra 1912 Cabang Medan - Ayub Tambak; Atika (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
Abstract This study aims to determine the factors that affect the underwriting surplus on the tabarru' fund in the sharia insurance company AJB Bumiputra1912 Syariah Medan branch. The factors contained in this study are the net contribution, claims expense, and the results of this research investment using descriptive qualitative research methods. By using analysis and interview methods and with previous data, this research was conducted so that the company could be stable in managing the underwriting surplus in tabarru funds, and could improve the quality and quality of the company, especially Ajb bumiputra1912 sharia field branch. Keyword: Surplus underwriting, sharia life insurance, tabarru' funds net contribution, claims and investment